2012
DOI: 10.1007/s10482-012-9763-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular sugar phosphates are assimilated by Streptomyces in a PhoP-dependent manner

Abstract: Filamentous microorganisms of the bacterial genus Streptomyces have a complex life cycle that includes physiological and morphological differentiations. It is now fairly well accepted that lysis of Streptomyces vegetative mycelium induced by programmed cell death (PCD) provides the required nutritive sources for the bacterium to erect sporeforming aerial hyphae. However, little is known regarding cellular compounds released during PCD and the contribution of these molecules to the feeding of surviving cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Additionally, phospho6sugars inhibit antibiotic production in streptomycetes. This effect is mediated by the phosphate6 rather than of the glyco6moiety, as the inactivation of phoP or ppk prevents or enhances, respectively, their utilization as nutrient sources and their inhibitory effect on antibiotic production 224 .…”
Section: Connections Between Phosphate Nitrogen and Carbon Metabolismmentioning
confidence: 99%
“…Additionally, phospho6sugars inhibit antibiotic production in streptomycetes. This effect is mediated by the phosphate6 rather than of the glyco6moiety, as the inactivation of phoP or ppk prevents or enhances, respectively, their utilization as nutrient sources and their inhibitory effect on antibiotic production 224 .…”
Section: Connections Between Phosphate Nitrogen and Carbon Metabolismmentioning
confidence: 99%
“…GlcNAc-dependent nutritional signaling is most likely mediated through changes in the intracellular level of GlcN-6-P, which binds as a ligand to the GntR-family regulator DasR, leading to derepression of DasR-mediated control of antibiotic production (Rigali et al, 2008). Recent work showed that addition of phosphorylated sugars to growth media under phosphate limitation delays the occurrence of the second round of PCD and results in vegetative arrest, also preventing antibiotic production (Tenconi, Jourdan, Motte, Virolle, & Rigali, 2012).…”
Section: Pcd and Antibiotic Productionmentioning
confidence: 99%
“…SYTO9 and SYTOX stained samples were examined at a wavelength of 488 for excitation and 530 nm (green) for emission. Red autofluorescence of PdGs and propidium iodide-stained samples were examined at a wavelength of 543 nm (Leica TCS-SP2) or 568 nm (Leica TCS-SP5) for excitation and 630 nm (red) for emission as described previously (64).…”
Section: In Situ Visualization By Confocal Fluorescence Microscopymentioning
confidence: 99%